2012
DOI: 10.1080/10538712.2012.726700
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Animal-Assisted Therapy in Group Treatment for Child Sexual Abuse

Abstract: This study evaluates and compares the effectiveness of three group interventions on trauma symptoms for children who have been sexually abused. All of the groups followed the same treatment protocol, with two of them incorporating variations of animal-assisted therapy. A total of 153 children ages 7 to 17 who were in group therapy at a Child Advocacy Center participated in the study. Results indicate that children in the groups that included therapy dogs showed significant decreases in trauma symptoms includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 29 publications
2
125
0
5
Order By: Relevance
“…All seven activity-based interventions [199][200][201][202][203][204][205] measured psychological distress. Two studies 201,203 also reported behaviour outcomes and one study 205 reported measures of social functioning and resilience.…”
Section: Activity-based Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…All seven activity-based interventions [199][200][201][202][203][204][205] measured psychological distress. Two studies 201,203 also reported behaviour outcomes and one study 205 reported measures of social functioning and resilience.…”
Section: Activity-based Interventionsmentioning
confidence: 99%
“…We identified six studies [199][200][201][202][203][204] that assessed the effectiveness of interventions that engaged the child in activity-based interventions, grouped as follows:…”
Section: Activity-based Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pet-assisted therapy for hospitalized children's with cancer has alleviated their emotional distress, facilitated their adaptation to the healing process and promoted their well-being [6]. Pet-assisted therapy on trauma symptoms for sexually abused children's have shown to decrease their trauma symptoms such as anxiety, depression, anger, post-traumatic stress disorder, dissociation, and sexual concerns [7]. Non-pet walkers are self-reported to possess risk indicators that may lead to diabetes mellitus, hypertension, hypercholesterolemia and depression compared to dog walkers [8].…”
Section: Modern Era: Sedentary Lifestylementioning
confidence: 99%